THE HIDDEN DETAILS OF HUMAN DIGNITY - Contreras Ugarte, Jesús Victor Alfredo (2019)
Human dignity means understanding human beings as beings that, due to its specific characteristics that are specific to the human condition, has a special value that requires recognition and respect from society. Human being would be placed in the center of the world, occupying a preeminent place with respect to the other beings. Thus, speaking of a human dignity of all human beings, equal for all as human beings, supposes placing ourselves in a universal and unified vision as to what it is. Here then, the problem begins. It is easy to find references to human dignity in many regulations, especially in human rights, both in national and international norms. In these regulations we will find, easily, the use of the term dignity repeated several times to sustain a certain right or legal argument, but not to define what is precisely and properly human dignity. Then, everything goes well as far as we assume that we all know and equally understand what dignity is; However, when you ask a direct question on what is human dignity? the issue is not as equally clear for everyone, nor is there uniformity in what is understood by it or, what is worse, you simply notice that they really do not know what it is and that they have never reflected on it. Here you discover this intrigue that is not easy to clarify. It seems a problem that some resolve one way, others in another and others do not. This work will try to shed light for the clarification of this conceptual complication.